COMPARISON OF LED VALUE FROM WESTERGREN METHOD WITH OPTICAL METHOD IN PJN HARAPAN KITA JAKARTA - Setiawan, Heru; Istiqomah, Nurul Hafifah (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Erythrocyte sedimentation rate (ESR) is a test of the rate at which erythrocytes settle in the plasma of a blood sample. Technical innovation in ESR inspection has greatly developed from semi-automatic to automatic methods. This research uses an experimental method which aims to determine the difference between the average ESR value of the Westergren method and the optical method and to determine patient characteristics through the ESR value at PJN Harapan Kita Jakarta. This study used 25 samples of heart disease patients diagnosed with CAD3VD, ADHF and MS Severe. Then a comparison test was carried out on the average ESR values ​​from two different methods, namely the Westergren method and the optical method. Significance analysis using the Mann-Whitney test obtained a p value of >0.05 indicating there was no significant difference between the average ESR value of the Westergren method and the optical method at PJN Harapan Kita Jakarta. The conclusion of this study is that there is no significant difference between the average ESR value of the Westergren method and the optical method at PJN Harapan Kita Jakarta and there is an increase in the ESR value in patients diagnosed with CAD3VD, ADHF or MS Severe.